Budding pouches and associated bubbles: 3D visualization of exo-membrane structures in plasmodium falciparum gametocytes - Hayakawa, Eri Saki H.; Wayama, Marina; Tokumasu, Fuyuki; Ohno, Nobuhiko; Matsumoto, Mami; Usukura, Jiro (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium falciparum gametocytes have unique morphology, metabolism, and protein expression profiles in their asexual stages of development. In addition to the striking changes in their appearance, a wide variety of “exo-membrane structures” are newly formed in the gametocyte stage. Little is known about their function, localization, or three-dimensional structural information, and only some structural data, typically two-dimensional, have been reported using conventional electron microscopy or fluorescence microscopy. For better visualization of intracellular organelle and exo-membrane structures, we previously established an unroofing technique to directly observe Maurer’s clefts (MCs) in asexual parasitized erythrocytes by removing the top part of the cell’s membrane followed by transmission electron microscopy. We found that MCs have numerous tethers connecting themselves to the host erythrocyte membrane skeletons. In this study, we investigated the intracellular structures of gametocytes using unroofing-TEM, Serial Block Face scanning electron microscopy, and fluorescence microscopy to unveil the exo-membrane structures in gametocytes. Our data showed “balloon/pouch”-like objects budding from the parasitophorous vacuole membrane (PVM) in gametocytes, and some balloons included multiple layers of other balloons. Furthermore, numerous bubbles appeared on the inner surface of the erythrocyte membrane or PVM; these were similar to MC-like membranes but were smaller than asexual MCs. Our study demonstrated P. falciparum reforms exo-membranes in erythrocytes to meet stage-specific biological activities during their sexual development.